2017
DOI: 10.3390/ijms18091836
|View full text |Cite
|
Sign up to set email alerts
|

Novel Drug Delivery Systems Tailored for Improved Administration of Glucocorticoids

Abstract: Glucocorticoids (GC) are one of the most popular and versatile classes of drugs available to treat chronic inflammation and cancer, but side effects and resistance constrain their use. To overcome these hurdles, which are often related to the uniform tissue distribution of free GC and their short half-life in biological fluids, new delivery vehicles have been developed including PEGylated liposomes, polymeric micelles, polymer-drug conjugates, inorganic scaffolds, and hybrid nanoparticles. While each of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 109 publications
0
38
0
3
Order By: Relevance
“…However, long-term application may become necessary in patients with refractory disease, and under such circumstances, GC therapy often has to be stopped due to adverse effects and second line therapy imitated. As an alternative, new strategies to prevent side effects of GC are currently being developed including the targeted delivery by nanocarrier systems [ 7 ]. For example, the application of a GC-copolymer conjugate has been found to ameliorate disease symptoms in a mouse model of IBD while preventing the development of osteoporosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term application may become necessary in patients with refractory disease, and under such circumstances, GC therapy often has to be stopped due to adverse effects and second line therapy imitated. As an alternative, new strategies to prevent side effects of GC are currently being developed including the targeted delivery by nanocarrier systems [ 7 ]. For example, the application of a GC-copolymer conjugate has been found to ameliorate disease symptoms in a mouse model of IBD while preventing the development of osteoporosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, to achieve a suitable timed-controlled drug release resulting in steady-state plasma concentration over a longtime period, some new and interesting drug delivery systems have been developed which aim at targeting specific cell types or tissues. It has been also proved that many novel carrier systems have improved pharmacokinetic and pharmacodynamic properties of various drug molecules [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoid treatment via injection plays a protective role by suppressing inflammation. However, several adverse effects including pain after drug injection, rupture of the Achilles tendon, skin atrophy, and depigmentation are induced by repetitive injections [7,8,16]. For these reasons, we examined whether DEX/ PMSs suppressed inflammatory responses and effectively prevented tendon degeneration in Achilles tendinitis models via the intratendinous treatment of DEX/PMSs.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the strong therapeutic effects, their longterm treatments affect tendon healing deleteriously and induce tendon rupture [7,8]. Mikolyzk et al [9] and Torricelli et al [10] suggested that glucocorticoid treatments reduces tendon strength and also inhibits proliferation and collagen synthesis of tenocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation